2020
DOI: 10.3389/fpsyg.2020.00494
|View full text |Cite
|
Sign up to set email alerts
|

Relating Lexical and Syntactic Knowledge to Academic English Listening: The Importance of Construct Representation

Abstract: This study aims to resolve contradictory conclusions on the relative importance of lexical and syntactic knowledge in second language (L2) listening with evidence from academic English. It was hypothesized that when lexical and syntactic knowledge is measured in auditory receptive tasks contextualized in natural discourse, the measures will be more relevant to L2 listening, so that both lexical and syntactic knowledge will have unique contributions to L2 listening. To test this hypothesis, a quantitative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
5
2
Order By: Relevance
“…However, these results do not support the findings of Mecartty (2000), Andringa et al (2012), Vafaee and Suzuki (2019) and Cai (2020), regarding the importance of grammar knowledge for L2 listening comprehension compared with the importance of vocabulary knowledge. The current study shows that both the scores of vocabulary test and the grammar test correlated significantly with L2 LC scores (r = .65 and r = .74, respectively).…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…However, these results do not support the findings of Mecartty (2000), Andringa et al (2012), Vafaee and Suzuki (2019) and Cai (2020), regarding the importance of grammar knowledge for L2 listening comprehension compared with the importance of vocabulary knowledge. The current study shows that both the scores of vocabulary test and the grammar test correlated significantly with L2 LC scores (r = .65 and r = .74, respectively).…”
Section: Discussioncontrasting
confidence: 93%
“…Meanwhile, Cai (2020) explored the correlation between lexical and syntactic knowledge with L2 LC and the unique contribution made by these two types of knowledge. The study recruited 258 Chinese learners of academic English and made use of a retired IELTS listening test to measure participants' L2 listening proficiency.…”
Section: Porta Linguarummentioning
confidence: 99%
See 2 more Smart Citations
“…The relative importance of lexical and syntactic knowledge in L2 listening test was investigated. It was found that both lexical and syntactic resources played an important role in successful L2 listening, and the role of lexical resources was more important than that of syntactic resources (Cai, 2020;Vafaee and Suzuki, 2020). Furthermore, empirical evidence showed that vocabulary knowledge is a strong predictor of L2 listening performance (Andringa et al, 2012;Matthews and Cheng, 2015;Wang and Treffers-Daller, 2017).…”
Section: Linguistic Demands (Task Input and Output)mentioning
confidence: 99%